The Relationship of Parents’ and Teachers’ Perceptions of Students’ Social-Emotional Development with Their Chinese Language Learning Achievement in Nursery 2 at a Trilingual International School in Bangkok - Li, Xin; Karnjanapun, Supit (Scholar: Human Sciences, 2021)
The purpose of this research were to examine the level of parents’ and teachers’ perceptions of students’ social-emotional development, and the relationship of the students’ social-emotional development with their Chinese language learning achievement of Nursery 2 (N2) at a trilingual international school in Bangkok. In this research, 81 parents and 28 teachers of 81 N2 students enrolled in the 2017-2018 school year in this school participated. This research followed a quantitative research methodology employing the questionnaires of parents’ and teachers’ perceptions of students’ social-emotional development, and the N2 Term 3 Chinese language summative assessment of the 2017-2018 school year to determine the level of students’ Chinese language learning achievement. There were four main elements included in this research: the level of parents’ and teachers’ perceptions of students’ social-emotional development, the level of Chinese language learning achievement, and the relationship between students’ social-emotional development and their Chinese language learning achievement. In this research, the students’ social-emotional development focused on three areas: paying attention-following direction, self-regulation, communication and interaction. Chinese language learning achievement focused on listening, speaking, communicating, also reading and tracing Chinese characters. There were four main findings: 1) the parents’ perception of students’ social-emotional development was on schedule; 2) the teachers’ perception of students’ social-emotional development was on schedule; 3) the students’ Chinese language learning achievement was exceeding the expectation; 4) there was a significant relationship of the parents’ and teachers’ perceptions of the students’ social-emotional development with their Chinese language learning achievement in N2 level at a trilingual international school in Bangkok.